The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1021/cn400153g
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Neural Cell Adhesion Molecule-Derived Peptide FGL on Seizure Progression and Cellular Alterations in the Mouse Kindling Model

Abstract: The neural cell adhesion molecule peptide mimetic fibroblast growth loop (FGL) proved to exert neuroprotective, neurotrophic, and anti-inflammatory effects in different in vitro and in vivo experiments. Based on this beneficial efficacy profile, it is currently in clinical development for neurodegenerative diseases and brain insults. Here, we addressed the hypothesis that the peptide might affect development of seizures in a kindling paradigm, as well as associated behavioral and cellular alterations. Both dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The CD200 expression on neuronal cells is regulated by the anti-inflammatory cytokine IL-4, in fact, IL-4 -/- mice display reduced CD200 expression, which increases when they are treated with exogenous IL-4 [ 86 , 87 ]. Recent studies have demonstrated that a peptide called FGL (fibroblast growth loop) is able to modulate the hippocampus inflammation, to regulate the activation of microglial cells both in vivo and in vitro [ 23 ]. FGL is a 15 mer fragment of neural cell adhesion molecule (NCAM) protein spanning residues Glu 681 –Ala 695 ; it is involved in the interaction between NCAM and fibroblast growth factor receptor (FGFR).…”
Section: Peptides and Peptidomimetics As Modulators Of Inflammatiomentioning
confidence: 99%
“…The CD200 expression on neuronal cells is regulated by the anti-inflammatory cytokine IL-4, in fact, IL-4 -/- mice display reduced CD200 expression, which increases when they are treated with exogenous IL-4 [ 86 , 87 ]. Recent studies have demonstrated that a peptide called FGL (fibroblast growth loop) is able to modulate the hippocampus inflammation, to regulate the activation of microglial cells both in vivo and in vitro [ 23 ]. FGL is a 15 mer fragment of neural cell adhesion molecule (NCAM) protein spanning residues Glu 681 –Ala 695 ; it is involved in the interaction between NCAM and fibroblast growth factor receptor (FGFR).…”
Section: Peptides and Peptidomimetics As Modulators Of Inflammatiomentioning
confidence: 99%